2021
DOI: 10.2147/ppa.s307091
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Interruption Among Drug-Susceptible Pulmonary Tuberculosis Patients in Southern Ethiopia

Abstract: Background: Tuberculosis treatment interruption is a failure of attending two scheduled appointments to collect the drugs in either phase of tuberculosis treatment. Even if TB treatment is crucial to achieve a cure and avoid the emergence of drug resistance, treatment interruption is the most testing and deterring factor for successful tuberculosis treatment and one of the problems leading to the development of drug-resistant tuberculosis. TB treatment interruption is the precursor for loss to follow-up and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Poorer treatment outcomes, including default treatment, mortality, and treatment failure, have been observed in TB patients who have consumed alcohol and MDR-TB, while treatment failure has been identified as a significant risk factor for drug resistance [ 38 ]. In addition, the consequences of alcohol ingestion can result in liver damage, weakened immunity, and nutritional deficiency, contributing to sensitive and resistant TB infection [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poorer treatment outcomes, including default treatment, mortality, and treatment failure, have been observed in TB patients who have consumed alcohol and MDR-TB, while treatment failure has been identified as a significant risk factor for drug resistance [ 38 ]. In addition, the consequences of alcohol ingestion can result in liver damage, weakened immunity, and nutritional deficiency, contributing to sensitive and resistant TB infection [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in India found that the majority of the LTFU patients investigated seem to complete at least the first two months of treatment (Ahmed and Mohan, 2021), while in a South African study it was found that the median period from treatment onset to LTFU was 101 days which, in turn, was linked to TB symptom relief (Kigozi et al, 2017). In a few instances, however, particularly in studies conducted in Ethiopia and India, the association between TB and treatment illiteracy and LTFU incidences was found to be meaningless (Tesfahuneygn et al, 2015, Workie et al, 2021.…”
Section: Tb Disease and Treatment Illiteracymentioning
confidence: 99%
“…Several studies have found that older age (ranging from >45 to >60 years) is associated with TB treatment LTFU (Chen et al, 2013, Patra et al, 2013, Lin et al, 2017, Mukhtar and Butt, 2017, Mundra et al, 2017, Muluye et al, 2018, while others linked this risk to younger age groups, mostly between 15 and 45 years (Marx et al, 2012, Nour El Din et al, 2013, Nglazi et al, 2015, Tesfahuneygn et al, 2015, Harling et al, 2017, Wohlleben et al, 2017, Mulongeni et al, 2019, Kimani et al, 2021. Some studies, on the contrary, found that age had no significant impact on TB treatment adherence, including more recent research conducted in several developing countries (Ajema et al, 2020, Robsky et al, 2020, Ahmed and Mohan, 2021, Iweama et al, 2021, Workie et al, 2021.…”
Section: Agementioning
confidence: 99%
“…Alcohol use is also an established risk factor for poor TB outcomes overall, including treatment failure, loss to follow up, and mortality for both drug-susceptible and drugresistant TB [102]. This is predominantly attributed to behavioral mechanisms, notably poor adherence to TB treatment and poor retention in TB care [102][103][104]. Outcomes are worse with common comorbid conditions, including HIV, hepatitis C, substance use, and smoking [105][106][107][108].…”
Section: Behavioral Mechanismsmentioning
confidence: 99%